PERBANDINGAN KEAKURATAN MODEL ARUS KAS METODE LANGSUNG LANGSUNG DAN TIDAK LANGSUNG DALAM MEMPREDIKSI ARUS KAS DAN DIVIDEN MASA DEPAN - Yustisa Taufik, 08.05.52.0199; Widati, Listyorini Wahyu (Students Journal of Accounting and Banking, 2012)
FASB assert that the direct method is more consistent with the purpose of cash flow, by providing information than the cash receipts and disbursements method of indirect (FASB, (1987). In other words, that the direct method cash flow information to better assess companyâs ability to pay dividends. The purpose of this study was to determine the predictive ability of cash flow information of direct and indirect method to predict cash flows and future dividends.The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) for the year 2007-2010. Sampling of this study using purposive sampling, the choice of subject groups based on traits-traits or specific properties, namely: the Company paid cash dividends from net income during the year 2007-2010, the companyâs financial statements using the currency of Indonesia and the companyâs operating cash flow does not lose. Samples used in this study were as many as 18 companies with 3 years of research into 54 observation data. Hypothesis testing with multiple linear regression.The result can be concluded that; 1) Model with a component of cash flows direct method is more accurate than the model with a component of cash flow indirect method to predict future cash flows. 2) Model with a component of cash flows direct method is more accurate than the model with a component of cash flow indirect method to predict future dividends.Keywords: Cash flows of direct and indirect method